Sudut Pandang Al-Ghozali Dalam Memaknai Spiritualitas Shalat - Fatakhul Huda (Taqorrub: Jurnal Bimbingan Konseling dan Dakwah, 2022)
One of the obligations of Muslims is prayer. Prayer is an obligation that requires the participation of two organs, namely the body and the heart. Even though he has prayed five times, his prayer cannot be said to be perfect if it is not accompanied by "the presence of the heart". The true value of worship is not judged from mere physical activity. The presence of the heart is another manifestation of the relationship between a servant and his Lord. The problem studied in this thesis is, what are the spiritual values ​​in prayer according to Al Ghazali's view. The purpose of this study was to find out how Al-Ghazali's view in interpreting the spiritual prayer. To reveal this problem in depth and comprehensively, the researcher uses a library method that is useful for providing information, facts and data regarding Al-Ghazali's views in interpreting the spiritual meaning of prayer, then the data is described, analyzed and discussed to answer these problems. problem. From the results of this study it was found that Al-Ghazali's view in interpreting the spiritual meaning of prayer lies in a servant who is able to carry out his prayers solemnly. Because we can solemnly feel the presence of God in front of us when we pray. The solemnity of a servant according to Al Ghazali can be achieved with six sentences, namely a servant who prays must be able to offer his heart, is Tafahhum, Takdzim, Haibah, Raja' and Haya'. The influence of prayer for humans is also felt by humans who are solemn in prayer. Among the effects, humans will be more disciplined in time because they feel supervised by Allah and will not waste valuable time. Second, humans are more humble because when the prostration of the feet and head are parallel, the third result is that humans will be protected from evil and evil deeds and by praying earnestly humans will be able to find peace in life and peace of mind.